Direct Three-Dimensional Observation of the Plasmonic Near-Fields of a Nanoparticle with Circular Dichroism - Jo, Jaeyeon; Ryu, Jinseok; Huh, Ji-Hyeok; Kim, Hyeohn; Seo, Da Hye; Lee, Jaewon; Kwon, Min; Lee, Seungwoo; Nam, Ki Tae; Kim, Miyoung (American Chemical Society, 2024)
Characterizing the spatial distribution of the electromagnetic fields of a plasmonic nanoparticle is crucial for exploiting its strong light-matter interaction for optoelectronic and catalytic applications. However, observing the near-fields in three dimensions with a high spatial resolution is still challenging. To realize efficient three-dimensional (3D) nanoscale mapping of the plasmonic fields of nanoparticles with complex shapes, this work established autoencoder-embedded electron energy loss spectroscopy (EELS) tomography. A 432-symmetric chiral gold nanoparticle, a nanoparticle with a high optical dissymmetry factor, was analyzed to relate its geometrical features to its exotic optical properties. Our deep-learning-based feature extraction method discriminated plasmons with different energies in the EEL spectra of the nanoparticle in which signals from multiple plasmons were intermixed; this component was key for acceptable 3D visualization of each plasmonic field separately using EELS tomography. With this methodology, the electric field of the plasmon that induces far-field circular dichroism was observed in 3D. The field linked to this chiroptical property was strong along the swirling edges of the particle, as predicted by a numerical calculation. This study provides insight into the correlation between structural and optical chiralities through direct 3D observation of the plasmonic fields. Furthermore, the strategy of implementing an autoencoder for EELS tomography can be generalized to achieve competent 3D analysis of other features, including the optical properties of the dielectrics and chemical states.